ANALYSIS FROM 1980 TO 2018 OF TIDAL OBSERVATION DATA FOR ASSESSING THE STABILITY OF TIDAL CONSTANTS FOR PRIMARY PORT - Morakinyo, Barnabas O. (FUDMA JOURNAL OF SCIENCES, 2024)
Tidal analysis involves the computation of tidal constants (phase lag (g) and amplitude (H)) of tidal constituents at a location. This study focuses on the assessment of the stability of g and H for the Bonny port which is the only standard tidal port in Nigeria. Monthly analysis of tidal observations was carried out with 1980, 1994 and 2018 year’s data using Least Squares Method (LSM) of Harmonic Analysis with MATLAB programming codes. The observation equation technique of LSM is adopted; the dimension of the Normal (N) matrix equations obtained for the monthly analysis is 72  56 i.e. 72 rows, and 56 columns. The N matrix is inverted and gave results for mean sea level (MSL) and g and H of 28 primary constituents of tide. Four major constituents of tide (M2, S2, K1 and O1) remain stable throughout the analysis. The mean of g and H obtained for each year was observed to be almost equal to the mean obtained from the three-year data. The maximum residuals and spreads of the computed g and H over the period of study show that g and H at Bonny are stable and that results from accurately analyze one-month data observation can be employed for tidal prediction for several years. Therefore, it can be concluded that the g and H for M2, S2, K1 and O1 are stable and that the type of tide (F) at Bonny port is semidiurnal since the computed F is 0.16 which is  0.25.
Keywords: Bonny port; Time series; Tidal constants; Least Squares Method (LSM); Standard port; Niger Delta